Giant Cell Tumor of the Patella: An Uncommon Site - Devkota, Karun; Bhattarai, Manoj; Adhikari, Kapil (Nepalese Journal of Radiology, 2018)
Primary tumors of the patella are rare of which Giant cell tumor is the most frequent. Patient usually presents with pain in anterior knee and swelling. Radiologically, Giant cell tumor usually presents as a well defined lytic lesion with no sclerotic margin, no periosteal reaction and no soft tissue involvement unless complicated by fracture and shows enhancement on post-contrast study. Herein, we report the case of a 31-year female with giant cell tumor of the patella (GCT) with its clinical and radiological features.